Intuitive understanding of steady‐state and transient behaviors. (April 2016) - Moxnes, Erling; Davidsen, Pål I.
Abstract: A growing literature demonstrates how most people misperceive structure and behavior of even simple dynamic systems. Developing an intuitive understanding of dynamics is also challenging for system dynamics students and teachers. The main purpose of this article is to contribute to intuitive understanding of steady‐state and transient behaviors. Analytical solutions to illustrative sample models are used to analyze these behaviors. The analysis explains why simple rules of thumb about exponential growth, exponential decay, and oscillations often fail to fully explain behavior in higher‐order models. The analysis highlights the role of initial stock values and of what we term "stock coordination". The exposed complexity of dynamics strengthens the need for simulations to test hypothesized explanations in terms of model structures. Copyright © 2017 System Dynamics Society